1988
DOI: 10.1180/claymin.1988.023.3.06
|View full text |Cite
|
Sign up to set email alerts
|

The nature of an iron oxide—organic iron association in a peaty environment

Abstract: Fe oxides deposited in ditches draining a bog in the Harz Mountains, Northern Germany, consist essentially of a two-XRD line ferrihydrite that has a magnetic hyperfine field of only 46·5 T at 4·2 K. Pyrophosphate extraction led to an incomplete separation of this from organically-bound Fe, which was depleted in the residue and particularly enriched in the dialysate of the extract. Decomposition of humics with H2O2 led to a further depletion of organic Fe, but also increased the number of XRD lines of the ferri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 12 publications
4
26
0
Order By: Relevance
“…Here small differences in the LHT-Q components for the surface and subsurface 4200 mm yr À1 site soils are consistent with an assignment of organic-Fe III complexes in the surface horizons and isomorphic substitution of Fe III in silicates in the subsurface soils. The carbon-rich (480 g kg À1 ) surface soil has a CS value of 0.53 mm s À1 , which is close to LHT CS values of 0.54 mm s À1 for organically-complexed Fe in peat soils reported by Schwertmann and Murad (1988). Whereas, the kaolinite/halloysite-rich subsurface soil has a CS of 0.48 mm s À1 , which is similar to that of 0.47-0.49 mm s À1 reported for kaolin-group minerals by Fysh et al (1983).…”
Section: Fe III -Silicate/organic-bound Fe Populationssupporting
confidence: 74%
See 1 more Smart Citation
“…Here small differences in the LHT-Q components for the surface and subsurface 4200 mm yr À1 site soils are consistent with an assignment of organic-Fe III complexes in the surface horizons and isomorphic substitution of Fe III in silicates in the subsurface soils. The carbon-rich (480 g kg À1 ) surface soil has a CS value of 0.53 mm s À1 , which is close to LHT CS values of 0.54 mm s À1 for organically-complexed Fe in peat soils reported by Schwertmann and Murad (1988). Whereas, the kaolinite/halloysite-rich subsurface soil has a CS of 0.48 mm s À1 , which is similar to that of 0.47-0.49 mm s À1 reported for kaolin-group minerals by Fysh et al (1983).…”
Section: Fe III -Silicate/organic-bound Fe Populationssupporting
confidence: 74%
“…Several recent studies have highlighted the effects of various organic components, organic matter and organic coatings on the magnetic properties of ferrihydrite (Schwertmann and Murad, 1988;Schwertmann et al, 2005;Eusterhues et al, 2008;Mikutta et al, 2008;Berquo et al, 2009;Michel et al, 2010). These studies illustrate that different carbon sources impact the Fh structure more substantially than others (Mikutta et al, 2008) decreasing Bhf between 1 and 3.5 T (Schwertmann et al, 2005;Eusterhues et al, 2008) and decreasing ordering temperature (T N ) up to 18 K. Even when changes to the Fh structure were minimal, Mikutta et al (2008) found dramatic changes in the point of zero charge, surface area and mineral porosity for organic-Fh co-precipitates.…”
Section: Characteristics Of Short-range-ordered Fe On the Mcgmentioning
confidence: 99%
“…The approximate ratio of width/length has been inferred from the saturation magnetization values, which are given in Figure 1 of Ricci and Kirschvink, 1992. s for macroscopic measurements to 10 -8 s for Mtssbauer spectroscopy (dashed curve in Figure 3), both greigites still lie within the SP region. This behavior is similar to that of a ferrihydrite--organic matter association, in which Schwertmann and Murad (1988) observed an enhancement of magnetic coupling across the ferrihydrite crystallites after removal of the organic matter.…”
Section: Width / Lengthsupporting
confidence: 64%
“…Dissolution of OC from organo-Fe(III) complexes by dithionite extraction is less clear but likely. Dithionite extraction almost fully dissolved precipitated, organically complexed Fe from a peat soil (Schwertmann and Murad, 1988). While dithionite effectively disperses Fe-cemented microaggregates (Pinheiro-Dick and Schwertmann, 1996), insoluble organic matter (e.g., plant detritus) in these aggregates will not appear in the dithionite-extractable phase.…”
Section: Introductionmentioning
confidence: 98%